Severe hereditary punctate palmoplantar keratoderma (Brauer-Buschke-Fischer syndrome) - Dorota Jaśkiewicz-Nyckowska; Aneta Szczerkowska-Dobosz; Marta Stawczyk-Macieja; Maria Czubek (Termedia Publishing House, 2015)
Introduction. Keratoderma of the hands and feet is a chronic disorder of epidermal keratinization, which consists of many various forms. Objective. To present a case of a 54-year-old woman with severe hereditary punctate palmoplantar keratoderma. Case report. The patient was admitted to the Department of Dermatology in Copernicus Hospital because of hyperkeratotic lesions on the hands and feet, with restriction of individual mobility. No coexisting malignancies or nail and hair disorders were diagnosed. Similar changes were found in many members of her family. Intensive topical treatment and oral therapy with retinoids were applied, resulting in a partial improvement. Conclusions. Hereditary punctate palmoplantar keratoderma is a rare disorder. Its long-term course and therapeutic difficulties significantly affect the quality of life.